The dynamic governance for basic education access of Indonesian migrant workers’ children in Malaysia - Neneng Heryati; Chandra Wijaya; Lina Miftahul Jannah (LPMPP Universitas Negeri Yogyakarta, 2026)
Indonesian Migrant Workers in Malaysia continue to face persistent challenges, particularly regarding access to basic education for their children in Sabah and Sarawak. These challenges arise from unclear legal status, limited educational infrastructure, low parental awareness, and weak educational governance. This study examines the implementation of dynamic governance at Community Learning Centers (CLCs) in Sabah and Sarawak as an adaptive strategy by the Indonesian government to ensure the fulfillment of the basic education rights of the children. Employing a qualitative and post-positivist approach, the data were collected through in-depth interviews and an extensive review of relevant literature. The findings reveal that the management of CLCs embodies dynamic governance characteristics, including adaptability, innovation, and collaboration, which are reinforced by national culture and identity: 1) adaptability to local regulatory environments and sociocultural contexts, 2) innovation in curriculum design and pedagogical methods, and 3) collaboration with multiple stakeholders involving the Indonesian and Malaysian governments, non-governmental organizations, and local communities. Furthermore, CLCs play a pivotal role in strengthening national identity among the children through the use of Indonesia’s national curriculum, the Indonesian language, and cultural activities, such as flag raising ceremony and Independence Day celebrations. Nevertheless, structural issues persist, including the lack of legal recognition, limited teaching staff, and inadequate facilities. The study underscores the necessity of dynamic, participatory, and sustainable governance to enhance access to basic education while reinforcing the cultural and national identity of the children of immigrant workers. The study encourages innovative governance models that can further improve educational access and equity for the children of immigrant workers in CLCs across Sabah and Sarawak.